Artistic system of author’s thinking “Notes from the Underground” by F. M. Dostoevsky and “A Hero of Our Time” by M. Yu. Lermontov. - Ayupov Timur Rustamovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to the problem of the genesis of the "underground man" type, the transformation of the Lermontov type of hero, presented by Pechorin, in "Notes from the Underground" by F.M. Dostoevsky. There is an opinion that any writer, as well as any "artist", has its own genealogy. In other words, every writer, portrait painter, architect, sculptor voluntarily or involuntarily draws on the experience of his predecessors and reflects it in one way or another in his work.